2020
DOI: 10.3390/app10072241
|View full text |Cite
|
Sign up to set email alerts
|

A Jumping Robot Driven by a Dielectric Elastomer Actuator

Abstract: Dielectric elastomer (DE) is a soft material that can deform to a large degree under the action of an electric field. In this paper, multilayer DE films were stacked in parallel to prepare a 20-layer dielectric elastomer actuator (DEA). This DEA could provide a peak output force of 30 N, which significantly improves the driving performance of the DEA and provides conditions for large load driving of the DEA. As a new driving method, the DEA was applied to a jumping robot, and the heavy-weight robot accomplishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…The design of the rolling module referred to the model of single pendulum structure, including counterweight (1), sheet metal (2), major shaft (3), bearing (4), drive motor (5), and bevel gear set (6), shown in Figure 2a. The drive motor (5), which was connected with the major shaft (3) through a bevel gear set (6), transmitted energy to the counterweight and housing through the bearing (5).…”
Section: Rolling Modulementioning
confidence: 99%
See 1 more Smart Citation
“…The design of the rolling module referred to the model of single pendulum structure, including counterweight (1), sheet metal (2), major shaft (3), bearing (4), drive motor (5), and bevel gear set (6), shown in Figure 2a. The drive motor (5), which was connected with the major shaft (3) through a bevel gear set (6), transmitted energy to the counterweight and housing through the bearing (5).…”
Section: Rolling Modulementioning
confidence: 99%
“…Compared with wheeled, tracked, or legged structures [2][3][4], they have smaller volume and higher fault tolerance. When facing rough terrain or large obstacles, jumping robots are obviously the most reasonable choice, which can surmount an obstacle of their own size, or even several times their own size [5].…”
Section: Introductionmentioning
confidence: 99%
“…Smart material actuation has emerged in recent 30 years [38]. The commonly intelligent materials including SMA, EAP, DEA, and so forth [103][104][105]. Because the intelligent material can be used as a CRs ontology or embedded in the robot body without rigid motor, and the energy source can be natural energy such as light, temperature or humidity.…”
Section: Smart Materials Drivenmentioning
confidence: 99%
“…Smart materials driven [102][103][104][105][106][107][108][109] Smart materials are usually used as raw materials for robots and play a role in the movement of robots. Under external stimuli, the robot will perform expected actions due to the properties of the material.…”
Section: Description Advantagementioning
confidence: 99%
“…Some authors demonstrated how DEAs can be used to manufacture lightweight fluid pumps (Mohd Ghazali et al, 2017;Cao et al, 2019;Linnebach et al, 2020), or showcased the possibility of generating high forces (Hau et al, 2018b). Further examples of DEA prototypes range from DE driven loudspeakers (Rustighi et al, 2018), contactors (Linnebach et al, 2019), and valves (Hill et al, 2017) to jumping devices (Luo et al, 2020) and medical systems (Goulbourne et al, 2003), to mention a few.…”
Section: Introductionmentioning
confidence: 99%